Innovations in food packaging - Han, Jung H. (Amsterdam : Academic Press, 2014)
This book examines the whole range of modern packaging options. It covers edible packaging based on carbohydrates,proteins, and lipids, antioxidative and antimicrobial
packaging, and chemistry issues of food and food packaging,such as plasticization and polymer morphology. The primaryfunctions of food packaging are to protect and preserve food quality and to enhance safety. To achieve these, packaging research has traditionally been focused on the developments of new barrier packaging materials and package designs. Since the late 90s, however, various innovations have been comprehensively studied and these emerging technologies have extended research topics from the primary function of food packaging to secondary functions including reduction of environmental impact, sales promotion and improvement of convenience for handling, distribution, and consumption
1. Physical chemistry fundamentals for food packaging -- 2. Active and intelligent packaging -- 3. Edible coating and films -- 4. Biopolymer packaging -- 5. Commercial food
packaging innovations
Includes bibliographical references
Keywords: Food -- Packaging; Food -- Packaging -- Technological innovations